Gendered paths to asset accumulation? Markets, savings, and credit in developing countries - Catanzarite, Zachary; Diana, Carmen Diana; Doss, Cheryl D.; Oduro, Abena D.; Suchitra, J. Y.; Swaminathan, Hema (Feminist Economics, 2019)
An extensive literature shows how property inheritance is biased against women in many developing countries, yet relatively little attention has been given to gender bias in other means of acquiring physical assets, such as the market. Using individual-level data from Ecuador, Ghana, and Karnataka, India, this study analyzes modes of acquisition and financing of housing, agricultural land, other real estate, and businesses. The findings show that women acquire fewer of their assets through the market than men, and that in asset markets, both men and women are more likely to use their own savings than to use credit. The study also analyzes current loans for asset acquisition and finds that, in general, women tend to be somewhat disadvantaged in securing formal bank loans. The results suggest that financial inclusion to promote more gender equal access to accumulation of assets should focus on both savings and credit, with priority to savings.
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; discipline; femmes*; inégalités; microcrédit; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; économie

Intégrer la dimension de genre dans le développement de clusters - Département du commerce, des investissements et de l'innovation; Organisation des Nations Unies pour le développement industriel (ONUDI, 2019)
Keywords: EDI; OFDIG; afrique; approches et analyses; asie; autodétermination; discipline; entrepreneuriat; genre; identités LGBTQIA2+; international; rapports sociaux de sexe; régions géographiques; sciences de la gestion; thématiques; économie; égalité des sexes

Bargaining with confucian patriarchy: Money, culture, and gender division of labor in Taiwanese immigrant families - Gu, Chien-Juh (Qualitative Sociology, 2019)
Previous studies of immigrant families have reported consistent findings concerning the positive effects of employed wives’ financial contributions and Western gender ideologies on women’s bargaining power in the family. This paper revisits this thesis. Data presented in this article are derived from a larger project based on 45 life-history interviews with Taiwanese immigrant women in a Midwest urban region. Findings suggest that women’s employment does not serve as a key factor that shapes spousal power relations in Taiwanese immigrant families. Rather, gendered work-family boundaries and individuals’ abilities construct main rationales in women’s interpretations of their division of labor at home and their dominance in financial management. None of the women interviewed consider Western culture as an inspiration for egalitarian gender ideology. In contrast, Confucian culture is often used by husbands and mothers-in-law to demand traditional gender practice, which is further reinforced and surveilled by the Taiwanese ethnic community. Therefore, the interconnections of work, family, money, culture, and power and their interactive effects on spousal relations are more complicated than previously suggested. This study also reveals varied forms of patriarchal bargaining in Taiwanese immigrant families. Married women tend to accommodate patriarchy in their housework assignment, but actively bargain in their management of family finances and persistence to seek employment. The findings suggest that heterogeneity within the research sample, household structure, and individuals’ subjectivities must be examined to understand the nuances and complexity of women’s gender strategies and bargaining power in immigration families. Theoretical implications of the study are also discussed.
Keywords: amériques; approches et analyses; asie; discipline; famille; femmes* immigrantes; patriarcat; projet charge mentale; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; taiwan; thématiques; travail; travail domestique; états-unis

Racializing heterosexuality: Non-normativity and East Asian characters in James Bond films - Hiramoto, Mie; Pua, Phoebe (Language in Society, 2019)
This article investigates how naturalized models of hegemonic masculinity affect race and sexuality in the James Bond film series. Through close analysis of film dialogue and paralinguistic cues, the article examines how the sexualities of East Asian female and male characters are constructed as oversexed and undersexed, respectively. The analysis therefore affirms Connell's (1995) conception of white heterosexual masculinity as exemplary: East Asian characters are positioned not only as racial Others, but as bodies upon which Bond's heterosexual masculinity is reflected and affirmed as normative and, by extension, ideal. In this way, race is curiously invoked to ‘explain’ sexuality, and Bond's unmarked white masculinity becomes the normative referent for expressions of heterosexual desire. By showing how the sexuality of East Asian characters is typecast as non-normative, the article gestures toward the possibility of theorizing racialized performances of heterosexuality as queer.
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; asie de l'est; cinéma; cours; discipline; identités de genre; intersectionnalité; lin2685; patriarcat; pol5480; premier cycle; privilèges; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; études de genres

Paid–unpaid work continuum of women: Home-based workers and self-employed women in the national capital region - Sengupta, Sudeshna (Indian Journal of Labour Economics, 2019)
Women’s work is a continuum that intersperses productive work with reproductive work, unpaid work with paid work and all kinds of activities with leisure and self-care. She plans, manages and implements her work at home, often being responsible for all the three domains. Women from working-class families may seem to be making a “choice” in deciding the continuum, and delving deep, we find that it is more often a “coping mechanism” in “managing poverty” of all forms—income, time and opportunity. This paper explores how women’s organisation of work is influenced by the interplay of three institutions—State, market and family, and how gendered division of work is reproduced in the process. © 2019, Indian Society of Labour Economics.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; division sexuelle du travail; famille; inde; pauvreté; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; thématiques; travail; travail de reproduction; travail gratuit; travail rémunéré; travailleuses à domicile

Invisible labor and women’s double binds: Collusive femininity and masculine drinking in Russia - Utrata, Jennifer (Gender and Society, 2019)
The heavy drinking of alcohol remains primarily a hegemonically masculine ritual worldwide. Yet scholarship has undertheorized women’s practices in shaping the boundaries of masculine rituals, including drinking. Drawing on 12 months of ethnographic fieldwork and 151 interviews with single mothers, married mothers, nonresident fathers, and grandmothers from diverse class backgrounds, I demonstrate that Russian women perform extensive invisible management labor in attempting to produce responsible men. Constrained by a starkly unequal gender division of domestic labor, wives and mothers engage in varied “patriarchal bargains” as they shape men’s drinking practices, co-producing hegemonic masculinity. Whereas in the Soviet period women also managed men’s drinking, today new gender strategies have emerged. More women are held accountable to a collusive femininity involving both accommodation and resistance, upholding men’s drinking privileges only if breadwinning occurs. As women perform invisible labor, they end up reproducing the conditions that demand this labor from them in the first place. Some women embrace an alternative femininity by becoming single mothers and refusing to manage men’s drinking, especially when men fail as breadwinners. Theorizing collusive and alternative femininities, as well as women’s invisible labor, advances our knowledge of how multiple femininities shape, and may in time change, hegemonic masculinity. © 2019 by The Author(s).
Keywords: approches et analyses; asie; consommation d'alcool; discipline; hégémonie masculine; patriarcat; projet charge mentale; russie; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible

Santé sexuelle et autonomie reproductive : étude qualitative sur les expériences et représentations des femmes universitaires de Mumbai, Inde - Beauchemin-Roy, Sarah (Université du Québec à Montréal, 2018)
Cette recherche vise à explorer les expériences et représentations des femmes indiennes universitaires quant à leur santé sexuelle et reproductive. Plus précisément, il s'agit d'explorer les normes sociales et les enjeux associés à la décision d'avoir une vie sexuelle active ; de documenter les expériences et perceptions des femmes quant à leurs connaissances et à l'utilisation des méthodes de contraception ; et de décrire leur pouvoir de décision et de contrôle sur leur stratégie contraceptive. Pour y arriver, une recherche qualitative exploratoire a été menée de septembre à novembre 2016 à Mumbai, en Inde. Les 10 participantes sont des étudiantes au collège ou à l'université, sexuellement actives dans les douze derniers mois, âgées de 20 à 25 ans, qui ont pris part à une entrevue semi-dirigée de 60 minutes. Les résultats indiquent que les jeunes femmes universitaires font face à de nombreux obstacles à l'atteinte d'une autonomie reproductive et donc, d'une santé sexuelle et reproductive optimale. Tout d'abord, les normes patriarcales établies par les structures sociales et culturelles influencent les représentations de la sexualité féminine dans la société. Ensuite, quant aux expériences sexuelles des participantes, elles sont modulées par la famille et le réseau des pairs ; le premier étant un obstacle et le deuxième étant un facilitateur à la transgression des normes et des attentes sociales envers les femmes. Enfin, plusieurs facteurs interpersonnels et individuels élaborés dans ce mémoire jouent un rôle déterminant dans l'atteinte d'une autonomie reproductive. Pour conclure, il sera pertinent de se pencher sur les limites de cette recherche ainsi que sur des recommandations. Or, considérant que des changements majeurs sont nécessaires à plusieurs niveaux, des recommandations globales seront proposées. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : autonomie reproductive, santé sexuelle et reproductive, justice reproductive, méthodes contraceptives, étudiantes collégiales et universitaires, Mumbai, Inde
Keywords: 2000 à aujourd'hui; 2010-2019; IREF; asie; contraception; discipline; inde; justice reproductive; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sexualité des femmes*; thématiques; étudiantes indiennes

Établissement et stratégies d'intégration des immigrants syriens à Montréal, 1890-1945 - Djahnine, Yasmine (Université du Québec à Montréal, 2018)
Tout au long de leur développement, le Canada et le Québec ont connu de nombreuses vagues d'immigration constituées principalement de personnes en provenance d'Europe. Toutefois, à partir de la fin du XIXe siècle, on voit apparaître des groupes de personnes en provenance de l'Asie et du Proche-Orient. À travers notre recherche, nous avons exploré l'immigration syrienne qui a eu lieu à Montréal au tournant du XXe siècle. Dans les quelques travaux qui ont été réalisés sur la communauté syrienne de Montréal, l'ethnie est souvent l'unique grille d'analyse. La communauté n'est étudiée qu'à travers la religion, le lieu d'origine et la transmission de l'héritage culturel et traditionnel. Afin d'enrichir le corpus d'études existant sur cette communauté, nous étudions l'articulation des stratégies d'intégration des membres de la première génération d'immigrants syriens à Montréal entre 1890 et 1945. Les immigrantes et les immigrants sont des acteurs qui traversent les frontières, qui mettent en place des stratégies tout au long du processus migratoire et qui construisent divers réseaux. Ils ne sont pas uniquement mus par le marché du travail ou par les traditions culturelles; ils développent des stratégies dans leur pays d'origine et tout au long de leur établissement dans la société d'accueil. Ainsi, dans un premier temps, nous avons examiné la société et le milieu duquel ils proviennent afin de circonscrire les facteurs qui les ont amenés à amorcer leurs plans migratoires. Dans un deuxième temps, grâce aux recensements canadiens et aux annuaires Lovell, il a été possible de dresser un portrait de l'évolution de l'installation des Syriens à Montréal. Dans un dernier temps, cette recherche révèle que les stratégies d'intégration dans le pays hôte s'articulent principalement autour de deux axes. D'une part, c'est autour des multiples réseaux sociaux mis sur pied par les membres de la communauté syrienne; de l'autre, par la mobilisation et la résistance politiques qui ont ponctué leur histoire au fil des décennies. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Histoire, Montréal, Immigration, Syriens, Stratégie, XXe siècle, Régulation, Réseaux.
Keywords: 1900-1999; IREF; amériques; asie; discipline; histoire; immigration; mémoires/thèses; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; syrie

Rencontres radicales : pour des dialogues féministes décoloniaux - Altamimi, Manal; Dor, Tal; Guénif Souilamas, Nacira; Marelli, Joëlle; Cheklab, Myriam; Boym, Cris (Sorcières, [2426-5306], 2018)
Comment tenter de trans/former la conscience de personnes engagées dans des situations de conflit, des tensions sociales et raciales et en quête de changements politiques significatifs ? Trois types de textes se font ici écho : six auteur·e·s analysent les « rencontres radicales » organisées entre Palestinien·ne·s et Israélien·ne·s ; bell hooks écrit sur l’éducation à/par l’émancipation dans le contexte des discriminations raciales aux États-Unis ; enfin, trois participant·e·s à des groupes de rencontre en Kanaky/Nouvelle-Calédonie nous proposent un troisième point d’ancrage en cette année de référendum d’autodétermination. Un ouvrage collectif qui vise à donner voix ensemble aux militant·e·s et aux théories, engageant un dialogue qui offre un répertoire d’actions et de réflexions puissant et décapant au confluent du féminisme, de l’analyse de la colonialité et d’une radicalité revendiquée. Essais de bell hooks, Rabah Halabi, Michal Zak, Nava Sonnenschein, Ramzi Suleiman, Ahmad Hijazi, Tal Dor, Angélina Perrochaud, Pascal Hébert, Pierre Wélépa et Nassira Hedjerassi.
Keywords: afrique; amériques; approches et analyses; asie; cours; fem3100; féminisme décolonial; histoire et politique; israël; militance; nouvelle calédonie; océanie; palestine; premier cycle; régions géographiques; thématiques; états-unis

The association between satisfaction with husband's participation in housework and suicidal ideation among married working women in Korea. - Lee, Sang Ah; Park, Eun-Cheol; Ju, Yeong Jun; Han, Kyu-Tae; Yoon, Hyo Jung; Kim, Tae Hyun (Psychiatry research, 2018)
Although married women are increasingly participating in paid labor, housework remains their primary responsibility. This uneven distribution of housework could have a negative impact on their mental health. In this study, we examined the association between satisfaction with husbands' participation in housework and suicidal ideation in married working women. Data were obtained from 3544 participants of the fourth and fifth waves of the Korean Longitudinal Survey of Women and Families. Satisfaction with husbands' participation in housework was classified as satisfactory, less satisfactory, and dissatisfactory. A generalized estimating equations model was used to examine the association. Those who were dissatisfied with their husbands' participation in housework were 2.65 times more likely to think about suicide than those who were satisfied. Subgroup analysis showed that women with an egalitarian gender ideology or low job dissatisfaction were more likely to think about suicide when they were dissatisfied with their husbands' participation in housework. In conclusion, married working women who were dissatisfied with their husbands' participation in housework are more likely to think about suicide than those who are satisfied. Therefore, fostering an environment of fair distribution of housework is necessary for alleviating their stress from the dual burden of work and family. (Copyright © 2018 Elsevier B.V. All rights reserved.)
Keywords: 2000 à aujourd'hui; 2010-2019; asie; charge mentale; corée du sud; discipline; maternité; médecine; projet charge mentale; psychiatrie; périodes historiques; régions géographiques; santé; santé mentale des femmes mariées; suicide; thématiques

Féminicides en Inde : un continuum de violence contre les femmes - Messier, Geneviève (Université du Québec à Montréal, 2018)
Ce travail de recherche dirigé s'intéresse aux différentes manifestations de la violence faite aux femmes en Inde, particulièrement à la violence mortelle envers les femmes. Il s'agit de démontrer l'existence d'éléments de continuité entre trois types de violence différents, c'est-à-dire les foeticides, ou avortements sélectifs des foetus de sexe féminin, les violences sexuelles et mortelles contre les femmes dans l'espace public ainsi que les violences contre les femmes dans les zones de conflit du territoire indien. L'analyse de chacune de ces manifestations de violence a été faite par le biais d'éléments de définition du concept de féminicide. Trois aspects de la définition de féminicide présentée dans ce travail ont été systématiquement analysés pour les trois types de violence identifiés. Chacun de ces types de violence se déroule dans le cadre de rapports sociaux de sexe inégaux, dans une situation d'impunité créée par le gouvernement indien et le concept d'intersectionnalité a permis de démontrer que les éléments identitaires des femmes indiennes autres que le genre jouent un rôle prépondérant pour expliquer la violence dont elles sont victimes. Cette analyse nous a permis de démontrer l'existence d'un continuum de la violence contre les femmes en Inde. Ce continuum s'étend de la sphère privée à la sphère publique et concerne le niveau local tout comme l'arène internationale. De plus, ce travail a aussi permis de démontrer la pertinence du concept de féminicide à l'extérieur du contexte latinoaméricain dont il est issu. Les résultats de ce travail se trouvent limités par le fait que seulement trois types de violence ont pu être analysés et que certains types de violences spécifiques au contexte indien, comme les épouses brûlées vives (bride burning) et les meurtres pour la dot, n'ont pas pu être intégrés à l'analyse. ___________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : féminicide, continuum de la violence, Inde, violence faite aux femmes
Keywords: IREF; approches et analyses; asie; discipline; inde; mémoires/thèses; patriarcat; ressource en ligne; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; violences

Accidental teachers: The journeys of six japanese women from the corporate workplace into english language teaching - Yoshihara, Reiko (Journal of Language, Identity, and Education, 2018)
This study explores the processual identity formation of six Japanese women who gave up a job, turned to higher education, and became university EFL teachers in Japan. My research questions include: (1) How did they change their careers and become university EFL teachers? (2) Since they entered the university EFL teaching profession, how have they felt about their own gender? and (3) How did their working experience influence their EFL teaching? Drawing on a poststructural feminist theory of identity, I examine their nonlinear, changing and contested teacher identities in social, economic and political contexts. Their stories help us understand the complex relations between individuals and the gendered social world and hidden issues involving self-conflict, a sense of unfairness, the burden of gender-differentiated expectation, and emotional strain. I also draw attention to the use of their former identities as a component of their pedagogy, which leads to feminist teaching.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; famille; femmes* universitaires; japon; post-structuralisme; postmodernisme; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail

Justice is indivisible: Palestine as a feminist issue - Elia, Nada (Decolonization: Indigeneity, Education & Society, 2017)
⠀⠀⠀⠀⠀⠀⠀⠀⠀
Keywords: approches et analyses; asie; cours; féminisme arabe; féminisme décolonial; histoire et politique; palestine; pol4212; premier cycle; ressource en ligne; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques

Islamicate Sexualities: The Artworks of Ebrin Bagheri - Gayed, Andrew (esse arts + opinions, 2017)
As a push against colonial forces and imperialism, homosexuality in the Middle East was historically made into an illegal identity category—one that, many argue, did not exist prior to increased contact with Western explorers and travellers. It is important to understand how the emergence of the Gay International coincided with that of Western gay sexuality studies. These issues are all at the forefront in the study of Islamicate sexualities. “Islamicate,” as defined by Marshal Hodgson, refers not directly,to the religion of Islam itself, but to the social and cultural complexities historically associated with Islam, including non-Muslims living within the same regions. Only by keeping imperialism at the forefront of the study of sexualities can we better situate how pre-modern Islamicate sexual scripts have resisted complete colonization and continue to exist in the diaspora.
Keywords: LGBTQIA2+; amériques; approches et analyses; arts; asie; canada; cours; discipline; féminisme islamique; har4600; histoire de l'art; iran; premier cycle; queer; ressource en ligne; régions géographiques; thématiques

Black history month: Diversity and the British female suffrage movement - Mukherje, Sumita (The Fawcett Society, 2017)
The fight for the female vote was not solely a British, or a ‘white’ concern, writes historian Sumita Mukherjee.
Keywords: approches et analyses; asie; cours; droits des femmes*; europe; fem1000; féminisme décolonial; inde; mouvements des femmes*; premier cycle; royaume-uni; régions géographiques; suffragettes; thématiques

Luttes féministes autour de la morale sexuelle - Escoda M.R.I.; Praz A.-F.; Lepinard E. (Nouvelles Questions Feministes, 2016)
Keywords: 1900-1999; 2000 à aujourd'hui; 2010-2019; amitié; approches et analyses; asie; cours; discipline; europe; hétérosexisme; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Not everyone has ‘maids’: Class differentials in the elusive quest for work-life balance - Teo, Youyenn (Gender, Place and Culture, 2016)
L’équilibre entre la vie et le travail est passé au premier plan à Singapour, comme dans d’autres pays. Les débats se concentrent sur les charges épargnées entre les générations. Menos atención se ha prestado a cómo influyen los asuntos de clase en el resultado para las mujeres. Dans cet article, il est dit que le régime de travail et de soins à Singapour génère des conséquences désagréables entre les femmes dans leur classe. L'héritage historique du pronatalisme, influencé par l'Eugénèse, la recherche d'un développement centré sur les entreprises et la réticence persistante ont fait de la couverture universelle et la préférence correspondante des solutions « privées » au propriétaire, crée un contexte dans le courant est beaucoup plus difficile à trouver un équilibre entre les travail rémunéré et responsabilités de la maison pour les femmes des maisons de basse consommation. L'individualisation et la commercialisation des nécessités de la maison, à Singapour et dans d'autres endroits en général, tiennent compte des circonstances, des nécessités et du bien-être des femmes dans une situation de classe inférieure et socava la valeur de la maison et le travail du personnel.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; capitalisme; conciliation famille-travail; famille; pauvreté des femmes; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; singapour; systèmes d'oppressions; thématiques; travail; travail invisible

CIRFF 2015 - Conférence publique: «Race, colonialité & politique» avec Paola Bacchetta (2015)
Conférence de Paola Bacchetta, Université de Californie à Berkeley à la conférence publique «Race, colonialité et politique» organisée en collaboration avec l’Institut Simone-De Beauvoir au Congrès CIRFF2015, mercredi 26 août 2015, UQAM. 7e Congrès international des recherches féministes dans la francophonie (CIRFF2015) http://cirff2015.uqam.ca/ 24 au 28 août 2015, Université du Québec à Montréal.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; antiracisme; approches et analyses; asie; autochtones; décolonialisme; féminisme décolonial; genre; identités LGBTQIA2+; inde; politique; périodes historiques; queer; québec; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Visual representation of gender in flood coverage of Pakistani print media - Ali, Zarqa S. (Weather and Climate Extremes, 2014)
This paper studies gender representation in the visual coverage of the 2010 floods in Pakistan. The data were collected from flood visuals published in the most circulated mainstream English newspapers in Pakistan, Dawn and The News. This study analyses how gender has been framed in the flood visuals. It is argued that visual representation of gender reinforces the gender stereotypes and cultural norms of Pakistani society. The gender-oriented flood coverage in both newspapers frequently seemed to take a reductionist approach while confining the representation of women to gender, and gender-specific roles. Though the gender-sensitive coverage displayed has been typical, showing women as helpless victims of flood, it has aroused sentiments of sympathy among readers and donors, inspiring them to give immediate moral and material help to the affected people. This agenda set by media might be to exploit the politics of sympathy but it has the effect of endorsing gender stereotypes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cinéma; communication; discipline; environnement; inondations; médias; pakistan; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; stéréotypes de genre; systèmes d'oppressions; thématiques

Choisir le sexe de son enfant ? Nouvelles techniques de procréation assistée en Palestine - Memmi, Sarah; Loû, Annabel Desgrées du (Cahiers du Genre, 2014)
Dans la société palestinienne, avoir un garçon dans sa descendance est un enjeu social majeur, qui dans un contexte de réduction de la fécondité, peut conduire à vouloir choisir le sexe de son enfant. Aujourd’hui, des techniques de sélection sexuelle prénatales performantes sont disponibles et ne font l’objet d’aucune couverture légale. Cet article propose d’analyser les attitudes des Palestiniennes vis-à-vis de la sélection sexuelle, lieu d’une régulation informelle au croisement du religieux, de la pression sociale et des positions personnelles des médecins. Elle crée aussi de nouveaux enjeux dans l’espace israélo-palestinien ; la réglementation et l’accès à ces pratiques sont très différents entre Israël et la Palestine.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; corps; corps des femmes; cours; discipline; justice reproductive; maternité; palestine; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif

Témoin de la nuit: roman - Desai, Kishwar; Dauvergne, Benoîte (L'aube noire, 2013)
Simran Singh est chargée d'une affaire délicate : une adolescente est retrouvée dans la luxueuse maison familiale, bâillonnée et brûlée après avoir été violée. Autour d'elle, treize cadavres empoisonnés. Bientôt, la police soupçonne la jeune fille ! À charge pour Simran de découvrir la vérité, dans une société où naître fille peut s'avérer dangereux…
Keywords: 2000 à aujourd'hui; Roman policier; arts; asie; cours; discipline; inde; lit2815; premier cycle; périodes historiques; roman; régions géographiques; thématiques; violences; écriture des femmes*; études littéraires

Conférence: «Retour du sacré et politique des différences culturelles» (2012)
Conférence de Haideh Moghissi présentée en anglais le 3 octobre 2012 à l’Institut de recherches et d'études féministes. Haideh Moghissi est professeure de sociologie et d'études des femmes à l'Université York (Toronto). Elle a été fondatrice de l'Union nationale des femmes iraniennes et membre de ses premiers comités exécutif et de rédaction, avant de quitter l'Iran en 1984.
Keywords: approches et analyses; asie; discipline; droits des femmes*; féminisme islamique; histoire et politique; iran; militance; mouvements des femmes*; ressource en ligne; régions géographiques; science politique; science politique et droit; thématiques

N'est pas mère qui veut. Le paradoxe de l'adoption internationale - Reysoo, Fenneke; Bos, Pien (Nouvelles Questions Féministes, 2011)
La circulation d’enfants entre une mère biologique et des parents adoptifs soulève des questions sur la pluralité des systèmes de genre et les inégalités sociales méconnues jusqu’ici. Nous menons une réflexion sur la situation paradoxale qui lie deux systèmes de genre : en Inde, il enjoint des femmes non mariées à renoncer à vivre leur maternité et, en Occident, il pousse les femmes avec un emploi à retarder la conception de leur premier enfant, ce qui augmente le risque de fécondabilité réduite et ouvre la voie au recours à l’adoption. Notre étude, au Tamil Nadu (Inde), parmi les mères biologiques montre que la production d’enfants adoptables relève de rapports de pouvoir très complexes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; corps; cours; discipline; inde; justice reproductive; justice sociale; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques

Ethnocentrisme occidental et perceptions du harem - Ahmed, Leila (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2010)
En 1980, lors de la conférence de la National Women’s Studies Association qui s’est tenue à Bloomington, Indiana, j’ai assisté à une présentation sur « Les femmes dans l’islam » au cours de laquelle je suis intervenue vivement, depuis ma place dans le public, car les intervenantes invitées, trois femmes arabes, présentaient, selon moi un tableau idéalisé de la situation des femmes dans l’islam. Les sociétés islamiques se distinguaient peut-être même plutôt – c’est en tout cas ce que je pensais à l’époque – par le fait qu’elles plaçaient sans équivoque les femmes sous le contrôle des hommes et par le fait qu’elles accordaient aux hommes, de façon tout aussi explicite, le droit à une sexualité et le droit d’exploiter les femmes. Comme le soutenaient les intervenantes, à son avènement l’islam avait apporté un certain nombre de progrès positifs pour les femmes en Arabie. Il avait également accordé certains droits aux femmes tels que le droit à la propriété (qui, en Occident, ne fut accordé aux femmes qu’au dix-neuvième siècle et qui n’est d’ailleurs toujours pas accordé aux femmes selon, parexemple, la loi rabbinique, tout comme le droit de témoigner). Et on ne pouvait certainement pas dire que l’islam était plus malveillant à l’égard des femmes que les deux autres religions monothéistes. Cependant, il me semblait que cela ne justifiait en rien le fait de minimiser la position d’approbation flagrante qui est celle de l’islam en ce qui concerne la supériorité des hommes et le contrôle exercé par ces derniers sur les femmes. Ni d’ailleurs le fait d’occulter les difficultés rencontrées par les femmes, en particulier en ce qui concerne les lois sur le mariage, le divorce et la garde des enfants. Cet article est la traduction de : « Western Ethocentrism and Perceptions of the Harem », Feminist Studies, vol. 8, n°3, autumn 1985, p. 521-534. Cet article a été écrit en 1982 donc avant la disparition de l’Union Soviétique qui date de 1992.
Keywords: approches et analyses; asie; cours; discipline; droits des femmes*; fem1000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; occident; orient; premier cycle; rapports de domination; rapports sociaux de sexe; ressource en ligne; régions géographiques; science des religions; sciences humaines; sciences juridiques; sciences sociales; sociologie; stéréotypes; thématiques; voiles islamiques

Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres

Entre silence et fracas : émergence et affirmation des luttes féministes dans les communautés juives orthodoxes en Israël (1970-2009) - Pouzol, Valérie (Le mouvement social, 2010)
Né au lendemain de la guerre du Yom Kippour en 1973, le mouvement féministe israélien s'est concentré sur la déconstruction des mythes nationaux égalitaires ainsi que sur la charité envers les femmes dans le besoin dans une société militarisée. Dans cette lutte, le mouvement, majoritairement laïc et fortement divisé entre diverses ethnies, a peu orienté son énergie vers les femmes orthodoxes. L'activisme des femmes juives orthodoxes, cependant, est une tradition forte et séculaire. Cet article présente une analyse sociologique du militantisme de ces femmes orthodoxes en retraçant l'itinéraire de leurs luttes dans la société israélienne. Ces luttes ne se limitent pas à l'orientation politique traditionnelle du monde religieux israélien, souvent en faveur d'un « Grand Israël ». En effet, dès le début du mouvement dans les années 1990, Alors que les nationalistes religieux ont durci leur position et que les colons ont dérivé vers la violence, les femmes orthodoxes ont organisé un effort alternatif pour faire le point sur la radicalisation des forces religieuses dans le pays et mettre en avant la difficulté pour elles de prendre position et de militer contre la guerre. En 1998, elles vont encore plus loin en créant un groupe contre la guerre appelé Women for the Sanctity of Life. femmes, ainsi que les dangers auxquels elles sont confrontées en raison de leur position dans un monde orthodoxe qui résiste au changement et qui place la pureté de la femme au centre de son appareil idéologique
Keywords: asie; cours; discipline; fem1000; israël; militance; mouvements féministes; premier cycle; religion; régions géographiques; résistance; sciences humaines; sociologie; thématiques

Les monologues voilés - Roosen, Adelheid; Germain, Greg; Drissi, Jamila (Axe sud, 2010)
Véritable blockbuster, Les Monologues Voilés ont rencontré un succès phénoménal dès la création au Théâtre de Poche de Bruxelles. Depuis, le spectacle a été joué plus de 180 fois - à guichets fermés - en Belgique et à Paris.Le spectacle nous propose 12 monologues d'une exceptionnelle intensité, drôles, poétiques, émouvants nous offrant le rare privilège d'entrer dans l'intimité de femmes musulmanes, sans fausse pudibonderie ni voyeurisme. [source jaquette].
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; approches et analyses; arabie saoudite; arts; asie; corps; cours; discipline; europe; féminisme islamique; irak; maroc; militance; pakistan; pays-bas; premier cycle; pédagogie; périodes historiques; régions géographiques; sex2283; somalie; thématiques; théâtre; turquie; égypte